RICHARD RORTY DAN RUANG PUBLIK PARA “PENYAIR”? : SEBUAH TEMATISASI KONSEP RUANG PUBLIK DI DALAM FILSAFAT POLITIK RICHARD RORTY - Antonius A.W., Reza (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2008)
How are we to define the concept of public sphere in contemporary society? How can we understand the drive that mobilizes it? And, how can we distinguish public life from the private ? This article follows Richard Roty's point of view in answering the questions. According to him, philosophers andsocial scientists have lost their monopoly in the process of defining public life. Their positions are replaced by poet, novelist, or journalist. The concept of public sphere is also changing, from 'rational' to 'poetic' public sphere. In the latter, public life is moved by contingency. The nature of humans and society is deprived from its metaphysical foundation. Rorty's ideas in this respect  may help identify what actually is happening in contemporary society.